Pengaruh Pembelajaran Berdiferensiasi Terhadap Kemampuan Membaca Siswa Kelas Iii Mata Pelajaran Bahasa Indonesia Di Minu Kh. Mukmin Sidoarjo - Khuluq, Muhammad Sahlul; Amin, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In this study, the researcher used quantitative methods, and used percentage and product moment analysis techniques. The subjects of this study were all students of class III MINU KH. Mukmin Sidoarjo with a total of 77 respondents. in this study there are 2 variables. Data collection in this study used observation, documentation, and questionnaires. In this study, the instrument used by the researcher was a questionnaire. For the questionnaire instrument, it was analyzed using Microsoft Excel and a calculator. Based on the formulation of problem number 1, namely, differentiated learning at MINU KH. MUKMIN Sidoarjo, the results were 76.92% which fell into the interval of 76% - 100% and fell into the Good category. Based on the formulation of problem number 2, namely, the literacy level of class III students in Indonesian subjects at MINU KH. MUKMIN Sidoarjo. the results were 79.29% which fell into the interval of 76% - 100% and fell into the Good category. Based on the formulation of problem number 3, differentiated learning has an effect on the reading ability of grade III students of MINU KH. Mukmin Sidoarjo. This is proven by the results of hypothesis testing using the product moment formula, obtained r count = 0.611 and r table = 0.224, because R count > R table (0.61 > 0.224) then the hypothesis ha is accepted which means there is an effect between differentiated learning on the reading ability of grade III students of MINU KH. Mukmin Sidoarjo. Based on the coefficient interval table, the amount of Rxy or R count of 0.611 is at the level of 0.60 - 0.799 and is categorized as Strong.